Detection of an HLA‐B*15 variant, HLA‐B*15:192, in a Taiwanese individual. (June 2018) - Yang, K. L.; Lin, P. Y.
Abstract : One nucleotide replacement at codon 145 of HLA‐B*15:01:01:01 results in a new allele, HLA‐B*15:192 .